The Poetics of Emptiness: The Aesthetic and Philosophical Functions of Blankness in the Paintings of Bada Shanren during the Qing Dynasty - Zhou, Yangyi; Kookiattikoon, Supath (Journal of Posthumanism, 2025)
This paper investigates the role of blankness (liú bái) in the representative paintings of Bada Shanren (Zhu Da), a key figure in early Qing dynasty literati art. Drawing on close visual analysis and grounded in Chinese aesthetic philosophy—particularly the concepts of xu (emptiness), wu (non-being), and yijing (poetic atmosphere)—the study explores how Bada Shanren transforms spatial voids into expressive agents of meaning. Five major works—Fish Swimming, Double Fish, Lotus and Duck, Rhododendron and Calligraphy, and Branch of Plum Blossoms—are examined to illustrate how blankness operates not as absence, but as presence: a space for emotional intensity, philosophical ambiguity, and subtle resistance. The paper argues that Bada’s use of blankness reflects both his inner psychological landscape and the socio-political dislocation following the fall of the Ming dynasty. Ultimately, the study demonstrates that Bada Shanren redefined blankness as a semiotic system in its own right, elevating silence, omission, and emptiness into a radical visual language unique in Chinese art history.